2006
DOI: 10.1089/neu.2006.23.1502
|View full text |Cite
|
Sign up to set email alerts
|

Aspects on Decompressive Craniectomy in Patients with Traumatic Head Injuries

Abstract: In patients with traumatic brain injury (TBI), intracranial hypertension secondary to cerebral edema is a major problem. A last-tier treatment in these cases is decompressive craniectomy. The aim of the present retrospective investigation was to (1) study the long-time outcome in patients with traumatic head injuries with intracranial hypertension treated with decompressive craniectomy; (2) examine the effects on intracranial pressure (ICP) by the craniectomy; and (3) investigate the possible relationship betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
1
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(64 citation statements)
references
References 35 publications
3
56
1
3
Order By: Relevance
“…1,2,4-7,9,11, [14][15][16]18,19,21,22,25,[27][28][29][31][32][33][34][35][36][37][38][39][40] The mean years of patient accrual were between 1987 and 2005. Total numbers in each GOS category are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…1,2,4-7,9,11, [14][15][16]18,19,21,22,25,[27][28][29][31][32][33][34][35][36][37][38][39][40] The mean years of patient accrual were between 1987 and 2005. Total numbers in each GOS category are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…This results in a dramatic reduction in the ICP and a reversal in the clinical and radiological signs of herniation [1] The concept of surgical expansion of the cranial cavity was fi rst expounded by Cushing, who used the procedure for the management of ICP due to brain tumors [2]. There has been a resurgence of interest in decompressive craniectomy for TBI in the past decade [3].…”
Section: Discussionmentioning
confidence: 99%
“…Each of those studies has used a different type and timing for the procedure, which makes it difficult to draw conclusions, but all procedures were effective at ICP reduction in cases of refractory intracranial hypertension [68][69][70]. The study by Taylor and colleagues demonstrated improved neurologic outcome in patients treated with decompressive craniectomy within 6 h of randomization in comparison to standard therapy [68].…”
Section: Decompressive Craniectomymentioning
confidence: 99%